The Project Approach for All Learners : a Hands-On Guide for Inclusive Early Childhood Classrooms. - Beneke, Sallee (Brookes Publishing, 2018)
This title provides early childhood educators with an in-depth understanding of how to implement the Project Approach with all students. A practical resource, it is designed with an Implementation Checklist, illustrative videos, training materials, Powerpoints, and downloadable forms to support application in inclusive settings.